2017
DOI: 10.1111/jace.15307
|View full text |Cite
|
Sign up to set email alerts
|

Strength of brittle materials in moderately corrosive environments

Abstract: The strengths of four brittle materials-cordierite glass ceramic, fused silica, silicon, and polycrystalline alumina were measured after exposure to weakly corrosive water and moderately corrosive buffered HF (BHF) solution. Exposure to water did not alter the strengths in subsequent inert strength tests and decreased the strengths in reactive strength tests. Exposure to BHF increased the strengths in both tests, but only after an incubation exposure time. Prior to the incubation time, the BHF had the same eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Unsurprisingly, the complicating factors required numerical solutions for strength predictions. A subsequent experimental work omitted microstructural effects and showed that constant stressing‐rate loading and long‐term zero‐stress aging in moderately corrosive environments could significantly affect reliability predictions through flaw alteration effects. Another work simplified consideration even further by omitting all effects of microstructure, contact‐flaw alteration, and crack‐velocity thresholds, to demonstrate a method for short‐term reliability prediction in reactive environments for components under constant applied stress containing contact flaws.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, the complicating factors required numerical solutions for strength predictions. A subsequent experimental work omitted microstructural effects and showed that constant stressing‐rate loading and long‐term zero‐stress aging in moderately corrosive environments could significantly affect reliability predictions through flaw alteration effects. Another work simplified consideration even further by omitting all effects of microstructure, contact‐flaw alteration, and crack‐velocity thresholds, to demonstrate a method for short‐term reliability prediction in reactive environments for components under constant applied stress containing contact flaws.…”
Section: Discussionmentioning
confidence: 99%
“…In constant stress studies, the failure time diverges as the applied stress approaches an analogous lower bound. For failure controlled by contact flaws, as is common in such tests, the lower bound reactive strengths are related to the upper bound inert strengths by the ratio (2 γ /2 γ 0 ) 2/3 , where 2 γ 0 is the surface energy of the material in an inert environment . For fused silica 2 γ 0 = 8.8 J m −2 and hence the strength ratio should be about 0.25 to 0.43 using the 2 γ estimates from above.…”
Section: Crack Propagation Parametersmentioning
confidence: 99%
“…Toughening and the formation of traction zones is minimized in materials with small or absent microstructural features, again similar to glasses. A material that meets these criteria, to be used here as an example, is a fine‐grained cordierite glass‐ceramic, similar to that studied earlier . The second two effects (3 and 4), thresholds and corrosion, depend on the mechanical and chemical environment.…”
Section: Introductionmentioning
confidence: 98%
“…Short failure times also minimize corrosion effects, as do environments that are reactive but do not remove material through dissolution. The second two criteria are met here by loading the samples in water to obtain failure times of 1 hour (threshold and corrosion effects are observed in cordierite in about 10 hours).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation